Gabriel Tarde’s Economic Psychology: A Radical Rethinking of Economic Reality - Katzarski, Ivan (Research Papers, 2018)
The study discusses major issues in Gabriel Tarde’s economic psychology. He is a scholar whose works are rediscovered by contemporary researchers and present a particular interest in the context of contemporary discussions on the grounds and perspectives of economic science. The paper aims at revealing this actuality of Tarde by analyzing his views on the status of political economy (economic theory) and his project concerning its reconstruction.The approach is one of content analysis of original texts, combined with an assessment of their contemporary significance. Both positive points of Tard’s conceptions and his conceptual shortcomings are pointed out.The study successively considers philosophical and sociological grounds of Tard’s economic psychology, his ideas of the relationship between the economic science and the other social sciences, his criticism of political economy and his vision of its reconstruction and his theory of prices which Illustrates the strong and weak points of his project. Tard’s economic psychology suggests original and valuable ideas which have been unreasonably neglected by historians of ideas and theoreticians. With its freshness and radical spirit, it can contribute to the contemporary theoretical debate.